Justification of the feasibility of developing the production of niche grains (Economics and region, 2023)
The presented study revealed the relevance of the development of the production of niche crops in general and niche cereals, in particular, in the changing conditions of today. The economic value and economic potential of niche grain crops is considered on the example of such an agricultural crop as oats. Revealing the potential of oats, outlined its advantages in the agronomic, ecological and economic plane. One of the main agronomic advantages of oats is determined to be undemanding to soil and climate. From the point of view of ecology and sustainable development, it is emphasized that oats can contribute to increasing biodiversity and improving the condition of soils. It is substantiated that the economic value of oats and the economic attractiveness of its production is largely due to its multifunctionality. First of all, the economic attractiveness of its production is determined by the possibility of its use for the production of healthy food. It has been established that the stable demand for oats and the economic attractiveness of its cultivation are due to its properties as a forage crop and an important cereal grain. Thus, the development of oat production, which is a representative of the group of niche grain crops, will allow to achieve a complex synergistic effect. The dynamics of oat production in Ukraine was studied in terms of agricultural enterprises, farms and households. It was found that the cultivation of oats in Ukraine is concentrated in households. Attention is paid to the regional aspect of oat cultivation in Ukraine. The dynamics of indicators of the economic efficiency of oat production in agricultural enterprises of Ukraine were analyzed. Factors restraining oat production in Ukraine are noted. The prospects for the development of the production of niche grain crops are outlined in the context of increasing biodiversity, diversifying Ukrainian agricultural production and export, and generally increasing the profitability of the grain industry. The main steps necessary for transferring the production of niche grain crops to the economically attractive category and achieving a synergistic effect have been determined.
Keywords: niche crops; niche grain crops; production dynamics; potential; economic efficiency